Understanding engagement in intensive learning: From fuzzy chaotic indigestion to eupeptic clarity - Dempsey Willis, Reilly A.; Vieira Braga, Paulo (Journal of University Teaching and Learning Practice, 2024)
This paper is framed by Nick Zepke’s, Vicki Trowler’s, and Paul Trowler’s concept of student engagement being “chaotic”, suffering from “indigestion” and “fuzziness”. This study was conducted at a UK higher education institution that recently moved to a “block and blend” delivery approach. We investigated what students and staff think engagement looks like in an intensive block and blend learning context. Data were gathered from students and staff via an online survey, which consisted of both scaled and open-ended questions. Findings are synthesised in an elemental map, providing a comparison of students and staff perceptions of engagement. Specifically, students and staff thought engagement in an intensive block and blend context entailed participation and active learning; a mindset that included enthusiasm, interest, focus, and enjoyment; timely completion of assessments; relationships with peers and tutors; doing more than required, such as completing extra readings; and accessing help and support. Participants also identified attendance as an indicator of student engagement and determined that the university has a responsibility to create learning environments to foster student engagement. Overall, the study findings point to elements of student engagement that may be designed into intensive block and blend learning environments. These approaches are also relevant to other similar intensive learning contexts.